Kausalitas Harga dan Permintaan Komoditas Pertanian di Provinsi Bengkulu - Andani, Apri; Nusril, Nusril; Rasyid, Witman (Jurnal Ekonomi dan Pembangunan Indonesia, 2017)
The research’s purpose is to find out a causality between price and demand on curly red chili, as well as between prices of commodities associated with it, and price formation correlation between markets. Data analysis method used is Granger causality and lag-test. The results show that there is no causality between price and demand of curly red chili in the province of Bengkulu. While the relationship between prices, there is one way relation between price of curly red chili with rawit chili and green chili on lag-2, and curly red chili price in some markets (origin and reference) have impact to another market (destination).